Right Brain Dominance in Infancy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The functional development of the left and right cerebral hemispheres in 39 normal children, aged 18 days to 19 years, was studied by measurements of cerebral blood flow at rest, using single photon emission computed tomography (SPECT), at the Neuropediatric Department, Hospital Saint Vincent de Paul, Paris, France.